2015
DOI: 10.1523/jneurosci.0004-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

PKMζ, But Not PKCλ, Is Rapidly Synthesized and Degraded at the Neuronal Synapse

Abstract: Synthesizing, localizing, and stabilizing new protein copies at synapses are crucial factors in maintaining the synaptic changes required for storing long-term memories. PKM recently emerged as a molecule putatively responsible for maintaining encoded memories over time because its presence correlates with late LTP and because its inhibition disrupts LTP in vitro and long-term memory storage in vivo.Here we investigated PKM stability in rat neurons to better understand its role during information encoding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 51 publications
1
32
5
Order By: Relevance
“…The kinase PKMζ has been implicated in long-term memory maintenance and is upregulated following neuronal activity (Shao, et al, 2012), but the function and precise sub-synaptic localization of these new PKMζcopies is unclear. We fused PKMζcDNA to a TimeSTAMP reporter, TS:YSOG3 (Palida, et al, 2015) that contains both YFP and miniSOG and allows newly synthesized proteins to be labeled in a drug-dependent manner using the small molecule BILN-2061. New copies can be visualized by correlated light and electron microscopy in a manner similar to previous TimeSTAMP reporters incorporating a split YFP and miniSOG (Butko, et al, 2012) (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinase PKMζ has been implicated in long-term memory maintenance and is upregulated following neuronal activity (Shao, et al, 2012), but the function and precise sub-synaptic localization of these new PKMζcopies is unclear. We fused PKMζcDNA to a TimeSTAMP reporter, TS:YSOG3 (Palida, et al, 2015) that contains both YFP and miniSOG and allows newly synthesized proteins to be labeled in a drug-dependent manner using the small molecule BILN-2061. New copies can be visualized by correlated light and electron microscopy in a manner similar to previous TimeSTAMP reporters incorporating a split YFP and miniSOG (Butko, et al, 2012) (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were treated 48 hours after transfection with 2 μM Arg 10 -IRDye 700DX (prepared in distilled water) and added to the culture media for 2 hours at 37 °C, after which time the media was removed and cells were rinsed once in HBSS. Primary mouse cortical neurons were cultured, transfected with TS:YSOG3-PKMζ, and chemically stimulated with 50 μM forskolin and 0.1 μM rolipram for 10 min, then incubated with 1 μM BILN-2061 as previously described (Palida, et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…The stability of PKMs has been an area of some controversy as they have been assumed to be quite stable for their role in the maintenance of memory, but some studies have shown relatively short half-lives (Palida et al 2015). In rodents and in Aplysia, PKM is stabilized through binding to the scaffold protein KIBRA, suggesting a model where correctly localized PKMs are stable, but free PKMs are degraded (Vogt-Eisele et al, 2014;Hu et al 2017b).…”
Section: Kibra Classical Calpain and Pkm Stabilitymentioning
confidence: 99%
“…The nascent PKMζ is then fully activated through co-translational phosphorylation by PDK1 (14) and stabilized by signaling mechanisms downstream of brain-derived neurotrophic factor (28) and by binding to the protein KIBRA (29). The newly synthesized, autonomously active PKMζ is then thought to be “tagged” to specific activated synapses, as shown by synaptic pathway–tagging experiments in hippocampal slices (30) and the translocation of newly synthesized PKMζ to postsynaptic sites during chemically induced LTP of primary cultured neurons (31). …”
Section: Pkmζ and Late Ltpmentioning
confidence: 99%